오염하천의 정화를 위한 파일럿 규모의 인공습지 적용 - 김승준; 최용수; 배우근 (한국물환경학회, 2006)
The purpose of this study is to improve the polluted stream water quality by pilot-scale five different constructed wetlands (CWs). Cell 1 to 3 are newly designed 2SFCW (Surface-subsurface flow CW) with 1 to 3 flow shifters (FS) in the middle of the wetland system. Cell 4 and 5 are control CW (CCW), but Cell 5 is the same type as Cell 3. The FS, which converts the route of surface and subsurface flow between two wetlands connected in series, was able to enhance the treatability of TN via nitrification and denitrification and of SS due to filtration and sedimentation. The void fraction and dispersion number of Cell 1, 2 and 3 obtained from the RTD analysis were found to be 0.73 and 0.17, respectively. COD and TP removal efficiencies of Cell 1 to 3 were similar to that of Cell 4 and 5. SS removal efficiencies of Cell 1 to 3 and 5 with FS were 5-10% higher than that of Cell 4 without FS. TN removal efficiencies of Cell 1 to 3 were 3-14% higher than that of Cell 4 and 5. The average R2 values of COD, SS, TN and TP obtained from nonlinear regression analysis were similar to the results of other researchers.